Accuracy analysis of measuring close-range image points using manual and stereo modes - Sužiedelytė-Visockienė, Jūratė (Geodesy and Cartography, 2013)
The performed investigations are aimed at estimating the accuracy of image processing using different image point measurements. For this purpose, digital close-range images were processed applying photogrammetric software PhotoMod. The measurements have been made employing two methods: stereo and manual mode. Two or more overlapping images are matched when control and tie points are estimated. The images of two objects have been taken for experimental investigation. Control points and tie points were measured switching either to stereo or manual mode applying the required software. The control points of the first object are distributed on the surface of a smooth facade and on the surface of different (a few) levels. The process of image matching includes the calculation of the correlation coefficient, vertical parallax residuals and the root mean square of the object. Following image transformation (adjustment processes) to the created 3D model, the accuracy of the measured points is determined. All these values show the precision of close-range photogrammetric processes. Such accuracy satisfies requirements for creating a proper digital terrain model and orthophoto generation.